Surface-Modified Adsorbent from Artocarpus heterophyllus Lam Biomass to Confine Reactive Red 194 in Real and Synthetic Effluents: Kinetics and Equilibrium Study - Lavanya Ramasamy; Lima Rose Miranda (Adsorption Science & Technology)
Chemical activation of Artocarpus heterophyllus Lam (jackfruit peel) via phosphoric acid was focused on this study for the preparation of activated carbon. Carbonization was done at a temperature of 400°C based on the nature of biomass after the impregnation ratio of 1 : 1 (weight of phosphoric acid/weight of raw material). Titanium dioxide was doped on the prepared activated carbon through the sol-gel method. Titanium dioxide doped activated carbon was synthesized to perceive the nature of adsorbents under ambient conditions. Both JPAC and JPAC/TiO2 adsorbents were characterized by the point of zero charges, Fourier transform of infrared spectroscopy, X-ray diffraction spectroscopy, Brunauer-Emmett-Teller analysis, and scanning electron microscopy with energy-dispersive X-ray analysis. The adsorption capacity of Reactive Red 194 (Red 2BN) dye on jackfruit peel activated carbon (JPAC) is 32.271 mg/g, and JPAC/TiO2 is 34.900 mg/g was observed under optimum conditions. Desorption efficiency of JPAC/TiO2 (≥93.4%) is slightly higher compared to JPAC (≥89.2%). Tannery effluents of various parameters were analyzed, and their chemical oxygen demand (COD) values trim down within the permissible limits of JPAC (97%) and JPAC/TiO2 (98%). Experimental data were studied using both two-parameter and three-parameter models of adsorption isotherm, namely, the Langmuir, Freundlich, Temkin, Dubinin-Radushkevich, Redlich-Peterson, Sips, Toth, and Khan. In which the Langmuir isotherm (R2=0.9824) best described the experimental data with an optimum monolayer capacity for adsorption capacity of 49.7 mg/g at 323 K on Red 2BN molecules. A proposed scheme of Red 2BN molecules on the active sites of adsorbents was illustrated. Regeneration of spent carbons was studied through different cycles of the run.